Multi-objective output feedback control strategy for a variable speed wind energy conversion system. (October 2020) - Watil, Aziz; El Magri, Abdelmounime; Raihani, Abdelhadi; Lajouad, Rachid; Giri, Fouad
Highlights: The paper presents an output feedback control for variable speed WECS based PMSG. The MPPT is achieved although mechanical and wind speed sensors are avoided. A high gain observer is employed to estimate the mechanical and electrical states. Integral sliding mode controller is designed based on the states estimations. The robustness of the output feedback controller is validated by simulation. Abstract: This paper deals with the problem of sensorless output feedback control for wind energy conversion systems (WECSs). The considered system consists of a synchronous aero-generator connected to the grid through an AC/DC/AC converter. Maximum wind energy extraction is achieved by running the wind turbine generator in a variable-speed mode without using a wind velocity sensor. This work establishes a different approach to estimate the rotor position, speed, and turbine torque. Furthermore, the proposed technique aims to provide an on-line estimation of the grid voltage and pulsation, considered generally as accessible. To overcome these issues, a high gain observer is designed. It provides estimates of all state variables, only from the current and voltage measurements. An integral sliding mode controller is then synthesized based on the estimation provided by the observer, with the view of ensuring the MPPT objective. Several simulations show that all control objectives are achieved and the output feedback performances enjoy robustness properties.